Regionalization of the Shark Hindbrain: A Survey of an Ancestral Organization - Rodríguez-Moldes, Isabel; Carrera, Ivan; Pose-Méndez, Sol; Quintana-Urzainqui, Idoia; Candal, Eva; Anadón, Ramón; Mazan, Sylvie; Ferreiro-Galve, Susana (Frontiers in Neuroanatomy, 2011)
Cartilaginous fishes (chondrichthyans) represent an ancient radiation of vertebrates currently considered the sister group of the group of gnathostomes with a bony skeleton that gave rise to land vertebrates. This out-group position makes chondrichthyans essential in assessing the ancestral organization of the brain of jawed vertebrates. To gain knowledge about hindbrain evolution we have studied its development in a shark, the lesser spotted dogfish Scyliorhinus canicula by analyzing the expression of some developmental genes and the origin and distribution of specific neuronal populations, which may help to identify hindbrain subdivisions and boundaries and the topology of specific cell groups. We have characterized three developmental periods that will serve as a framework to compare the development of different neuronal systems and may represent a suitable tool for comparing the absolute chronology of development among vertebrates. The expression patterns of Pax6, Wnt8 and Hoxa2 genes in early embryos of S. canicula showed close correspondence to what has been described in other vertebrates and helped to identify the anterior rhombomeres. Also in these early embryos, the combination of Pax6 with protein markers of migrating neuroblasts (DCX) and early differentiating neurons (general: HuC/D; neuron type specific: GAD, the GABA synthesizing enzyme) revealed the organization of S. canicula hindbrain in both transverse segmental units corresponding to visible rhombomeres and longitudinal columns. Later in development, when the interrhombomeric boundaries fade away, accurate information about S. canicula hindbrain subdivisions was achieved by comparing the expression patterns of Pax6 and GAD, serotonin (serotoninergic neurons), tyrosine hydroxylase (catecholaminergic neurons), choline acetyltransferase (cholinergic neurons) and calretinin (a calcium-binding protein). The patterns observed revealed many topological correspondences with other vertebrates and led to re